Responses of different okra (Abelmoschus esculentus) cultivars to water deficit conditions - Ayub, Q; Khan, S M; Hussain, I; Naveed, K; Ali, S; Mehmood, A; Khan, M J; Haq, N U; Shehzad, Q (Journal of Horticultural Sciences, 2021)
A pot experiment was conducted to evaluate the adverse effects of drought on different okra cultivars and to identify the most suitable okra cultivar for growing in drought conditions. Five okra cultivars namely Pusa Green, Clemson, Sabz Pari, Pusa Swani and Mehak Pari were subjected to three drought levels i.e., control (100% Field capacity),50% and 25% Field Capacity (FC). Physiological parameters like fresh and dry weight of plant and plant height were recorded along with biochemical attributes such as chlorophyll content (a, b, total) carotenoids, total protein, proline content, and Membrane stability index (MSI%). Results showed that drought significantly reduced all the studied parameters and at maximum drought (25% FC) lowest values of fresh weight (12.42g), dry weight (1.22g), plant height (7.86cm), chlorophyll a (9.02mg/g FW), chlorophyll b (18.69mg/g FW), total chlorophyll (27.71mg/g FW), carotenoids (11.80mg/g FW), total protein (2.73mg/g FW),whereas maximum Proline (21.36μg/g FW), and MSI (72%) were observed under the same drought. The results concerning responses of okra cultivars under drought conditions showed that maximum. Fresh weight (15.25g) and Dry weight (2.74g) was observed in Pusa green while maximum Plant height (13.77cm), Chlorophyll a (14.38mg/g FW), Chlorophyll b (24.41mg/g FW), Total Chlorophyll (38.80mg/g FW), Carotenoids (18.57mg/g FW), Total Protein (5.44mg/g FW), Proline (27.78μg/g FW), and MSI (56.33%) were produced by Sabz Pari. Hence it can be concluded that drought causes significant variation on physical and biochemical attributes of okra whereas Sabz Pari showed resistance towards the applied stress and produced better results.
Keywords: Drought; Okra; Oxidative Stress; Proline content